Open reduction and internal fixation of paediatric maxillozygomatic complex fractures: An 11-year multicentric retrospective study - Roccia, Fabio; Sobrero, Federica; Strada, Carlo; Bottini, Gian Battista; Goetzinger, Maximilian; Samieirad, Sahand; Vesnaver, Aleš; Birk, Anže; de Oliveira Gorla, Luis Fernando [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP]; Dediol, Emil; Kos, Boris; et al. (Wiley, 2024)
Background/aim: Paediatric maxillozygomatic complex (MZC) fractures are uncommon, and there is a scarcity of data regarding their surgical treatment. The aim of this study was to analyse choices and outcomes of open reduction and internal fixation (ORIF) for MZC fractures among 14 maxillofacial centers around the world. Materials and Methods: This multicentric retrospective observational study included patients ≤16 years of age with quadripod MZC fractures treated with ORIF from January 2011 and December 2022. The following data were collected: age, gender, dentition stage (deciduous, mixed, and permanent), cause of injury, type of fracture, surgical approach, site of osteosynthesis (infraorbital rim, zygomaticomaxillary buttress, frontozygomatic, and zygomaticotemporal sutures), material (titanium or resorbable) and number of plates used, and outcome. The minimum follow-up was 6 months. Statistical analyses were performed with Fisher's exact test or chi-squared test, as appropriate. Results: Sixty-four patients (mean age, 12.3 years) with quadripod MZC fractures were included. Seventy-two percent of patients received a single-point fixation. The zygomaticomaxillary buttress was the most common site for fixation, both in single-point and two-point fixation schemes, especially in combination with the frontozygomatic suture. Increasing age was associated with a higher rate of plate removal (p <.001). Postoperative complications included 5 (7.8%) cases of wound infections, 2 (3.1%) infraorbital paraesthesia, 1 (1.6%) ectropion. Residual facial asymmetry was found in 5 (7.8%) patients and was not associated with the type of fixation (p >.05). Conclusions: This study highlights the possibility of using ORIF, even with a single point of fixation, for the treatment of displaced quadripod MZC fractures in the paediatric population. The zygomaticomaxillary buttress was the preferred site of fixation and allowed for adequate stabilization with no external scars and a low risk of tooth damage. Future prospective studies with long-term follow-up are needed to establish definitive surgical protocols and clarify the surgical decision-making.
Keywords: adolescent; child; fracture fixation; maxillary fractures; zygomatic fractures